The Influence of Korean Wave, Brand Ambassador, Koreanesque Brand Image of local cosmetic and Product Price on Purchase Intention of Local Cosmetic - Listia Amalia; Desty Kusuma Wulandari; Deddy Kusuma Hadiputra; Pantri Heriyati (Green Publisher Indonesia, 2024)
The influence of the Korean Wave, brand ambassadors, and Koreanesque brand image has significantly shaped consumer behavior in Indonesia’s local cosmetic market. This study aims to analyze the impact of these factors along with product pricing on purchase intention for local cosmetics inspired by Korean culture. Using a quantitative approach, data was collected through online questionnaires distributed to 321 respondents, with 200 valid responses analyzed using SmartPLS 4.0. The results indicate that brand image and product price have a significant positive effect on customer trust and purchase intention, while the Korean Wave and brand ambassadors show no direct influence when mediated by customer trust. The findings suggest that local cosmetic companies should emphasize building a strong Koreanesque brand image and competitive pricing strategies to enhance purchase intention and foster consumer loyalty.